2024
DOI: 10.1039/d4gc00308j
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of C20- and C22-polyunsaturated fatty acids and fish oil hydrolyzates to R,R-dihydroxy fatty acids as lipid mediators using double-oxygenating 15R-lipoxygenase

Jin Lee,
Yoon-Joo Ko,
Jin-Byung Park
et al.

Abstract: C20- and C22-dihydroxy fatty acids (DiHFAs) are bioactive lipid mediators (LMs) in humans. Among them, leukotrienes are inflammatory mediators, whereas resolvins generated by M2 macrophages in humans are anti-inflammatory mediators....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The ndings suggested that the most effective ratios of cells to substrate for producing RvE4 and its enantiomer were 1:4 and 1:3 (g L −1 per mM), respectively. SP825 was chosen as the absorbent resin for converting EPA into RvE4 and its enantiomer due to its superior binding capacity for ARA compared to other tested resins, including HP20, SP2MG, SP207, SP825, and SP850 (Lee et al 2024).…”
Section: Optimization Of Cell Substrate and Resin Concentrations To E...mentioning
confidence: 99%
“…The ndings suggested that the most effective ratios of cells to substrate for producing RvE4 and its enantiomer were 1:4 and 1:3 (g L −1 per mM), respectively. SP825 was chosen as the absorbent resin for converting EPA into RvE4 and its enantiomer due to its superior binding capacity for ARA compared to other tested resins, including HP20, SP2MG, SP207, SP825, and SP850 (Lee et al 2024).…”
Section: Optimization Of Cell Substrate and Resin Concentrations To E...mentioning
confidence: 99%